Sikkerhed, sprog og ret - Ugilt, Rasmus (Slagmark - Tidsskrift for idéhistorie, 2018)
The article discusses the theoretical differences of Schmitt and Agamben and argues that, even though Agamben is clearly inspired by the German jurist, crucial points are lost if one does not take care to notice the crucial differences between them. Schmitt’s idea that sovereignty is a paradox is shared by Agamben, but the latter draws quite different consequences from this idea than does the former. What distinguishes Agamben from Schmitt can be described as a certain form of inactivity of power. It is in the question about the activity and the inactivity of power that the theoretical discussion about the two thinkers is to be settled. I argue that this should lead us to choose Agamben ahead of Schmitt as our theoretical guide to the juridico-political situation we find ourselves in 10 years after 9/11.